Bacillus subtilis SL18r Induces Tomato Resistance Against Botrytis cinerea, Involving Activation of Long Non-coding RNA, MSTRG18363, to Decoy miR1918 - Zhou, Cheng; Zhu, Jingjing; Qian, Nana; Guo, Jiansheng; Yan, Congsheng (Frontiers in Plant Science, 2021)
Mounting evidence has indicated that beneficial rhizobacteria can suppress foliar pathogen invasion via elicitation of induced systemic resistance (ISR). However, it remains elusive whether long non-coding RNAs (lncRNAs) are involved in the mediation of the rhizobacteria-primed ISR processes in plants. Herein, we demonstrated the ability of the rhizobacterial strain Bacillus subtilis SL18r to trigger ISR in tomato plants against the foliar pathogen Botrytis cinerea. Comparative transcriptome analysis was conducted to screen differentially expressed lncRNAs (DELs) between the non-inoculated and SL18r-inoculated plants. Among these DELs, four variants of MSTRG18363 possessed conserved binding sites for miR1918, which negatively regulates immune systems in tomato plants. The expression of MSTRG18363 in tomato leaves was significantly induced by SL18r inoculation. The transcription of MSTRG18363 was negatively correlated with the expression of miR1918, but displayed a positive correlation with the transcription of the RING-H2 finger gene SlATL20 (a target gene of miR1918). Moreover, MSTRG18363-overexpressing plants exhibited the enhanced disease resistance, reduction of miR1918 transcripts and marked increases of SlATL20 expression. However, the SL18r-induced disease resistance was largely impaired in the MSTRG18363-silenced plants. VIGS-mediated SlATL20 silencing also greatly weakened the SL18r-induced disease resistance. Collectively, our results suggested that the SL18r-induced expression of MSTRG18363 promoted the decoy of miR1918 and mediated the expression of SlATL20 in tomato plants, thereby effectively provoking ISR against pathogen infection.